Facing the Second World War strategy, politics, and economics in Britain and France, 1938-1940 - Imlay, Talbot C. (Oxford University Press, 2003)
This work offers a systematic comparison of how two countries, Britain and France, responded to the possibility and then reality of total war by examining developments in three dimensions: strategic, domestic political, and political economic.